THE IMPACT OF CONFLICTS AND PROBLEMS BETWEEN PARENTS ON THE PSYCHOLOGY OF CHILDREN (Universal International Scientific Journal, 2026)
This article analyzes the psychological impact of parental conflict and problematic situations in the family on children's psyche. Disagreements, quarrels, and a conflictive environment in the family can negatively affect the emotional state, behavior, and social development of children. The study highlights the fear, anxiety, aggression, and self-doubt that arise in children due to parental conflict. It also emphasizes the importance of creating a positive atmosphere in the family for the healthy psychological development of children.
Keywords: family; parental conflicts; child psychology